Primary Neuroendocrine Tumor of the Left Hepatic Duct: A Case Report with Review of the Literature - Bhandarwar, Ajay H. (Hindawi Publishing Corporation, 2012)
Primary Biliary Tract Neuroendocrine tumors (NET) are extremely rare tumors with only 77 cases been reported in the literature till now. We describe a case of a left hepatic duct NET and review the literature for this rare malignancy. To the best of our knowledge the present case is the first reported case of a left hepatic duct NET in the literature. In spite of availability of advanced diagnostic tools like Computerized Tomography (CT) Scan and Endoscopic Retrograde Cholangio Pancreaticography (ERCP) a definitive diagnosis of these tumors is possible only after an accurate histopathologic diagnosis of operative specimens with immunohistochemistry and electron microscopy. Though surgical excision remains the gold standard treatment for such tumors, patients with unresectable tumors have good survival with newer biologic agents like Octreotride.